An Investigation into the Plant Requirements of Zizyphus jujuba during Growth and under Lac Cultivation, Part I - Norris, Dorathy; Rangaswami, M.; Venugopalan, M.; Ranganathan, S. (Indian Forester, 1929)
No abstract